2019
DOI: 10.1177/0036850419884873
|View full text |Cite
|
Sign up to set email alerts
|

Endangered elements, critical raw materials and conflict minerals

Abstract: Amid present concerns over a potential scarcity of critical elements and raw materials that are essential for modern technology, including those for low-carbon energy production, a survey of the present situation, and how it may unfold both in the immediate and the longer term, appears warranted. For elements such as indium, current recycling rates are woefully low, and although a far more effective recycling programme is necessary for most materials, it is likely that a full-scale inauguration of a global ren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 84 publications
0
23
0
Order By: Relevance
“… 8 This CE approach strives to slow, narrow and close socioeconomic material cycles, 9 by reducing absolute material flows. 3 , 7 , 10 It is fundamentally different to a traditional linear economy whereby raw materials are collected, transformed into products, used once, and discarded as waste.…”
Section: Introductionmentioning
confidence: 99%
“… 8 This CE approach strives to slow, narrow and close socioeconomic material cycles, 9 by reducing absolute material flows. 3 , 7 , 10 It is fundamentally different to a traditional linear economy whereby raw materials are collected, transformed into products, used once, and discarded as waste.…”
Section: Introductionmentioning
confidence: 99%
“…Following the onset of the global financial crisis in 2008, officials United Nations Environment Program (UNEP) reported that certain metals were critical for the electronics industry, including Ta, In, and Ru. They also drew attention to how these metals were also important for photovoltaic technologies, batteries, platinum group metals, and rare earth elements in general ( Rhodes, 2019 ).…”
Section: The Lack Of Essential Raw Materials Post-covid-19mentioning
confidence: 99%
“…In June 2011, the European Union (EU) published a report which identified 14 critical raw materials vital to countries comprising the zone. It included detailed information about essential supply and demand, sharing statistics, as well as insights on how to obtain these resources through the circular economy (i.e., through electronic waste recycling) ( Rhodes, 2019 ). Senior EU officials expressed concern from possible supply restrictions for environmental reasons.…”
Section: The Lack Of Essential Raw Materials Post-covid-19mentioning
confidence: 99%
“…The majority of publications are focused on material recycling and recovery: (a) in general [7,48,84], (b) of blade materials [47,[85][86][87][88][89][90][91][92][93][94][95][96] or (c) of critical raw materials [97][98][99][100][101][102][103][104][105]. Joining up the start and the end of low-carbon infrastructure supply chains, resource security concerns [102,106,107], design for recycling [108,109] and supply chain security and development [95,103] are covered.…”
Section: Current Circular Economy Literature On Wind Energymentioning
confidence: 99%